1995
DOI: 10.2190/fyar-weye-m1t8-7mf3
|View full text |Cite
|
Sign up to set email alerts
|

Risks Associated with Long-Term Homelessness among Women: Battery, Rape, and HIV Infection

Abstract: The purposes of this study were to determine the prevalence of battery, rape, and HIV risk practices in a sample of long-term homeless women and to explore correlates of HIV risk practices. Fifty-three women who had been homeless for at least three months in the last year were interviewed at day and night shelters. The women were demographically similar to other samples of homeless men and women and had similar rates of drug use. However, a higher proportion of homeless women were exposed to battery (91 percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 42 publications
1
33
0
Order By: Relevance
“…Previous studies have documented that such conditions in women's lives are linked to an increased risk of partner violence, [3][4][5][6][7][8]10,21,[24][25][26][27][28] but no study to date has linked these conditions in a population of HIV-infected men. Furthermore, after control for socioeconomic factors, drug use, and CD4 cell count, Hispanic men with male sexual partners were at greater risk for violence than men of other race/ethnicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have documented that such conditions in women's lives are linked to an increased risk of partner violence, [3][4][5][6][7][8]10,21,[24][25][26][27][28] but no study to date has linked these conditions in a population of HIV-infected men. Furthermore, after control for socioeconomic factors, drug use, and CD4 cell count, Hispanic men with male sexual partners were at greater risk for violence than men of other race/ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Overlapping risk factors include poverty, unemployment, drug dependency, childhood sexual and physical abuse, being younger than 30 years, and homelessness. [3][4][5][6] Violence and HIV also may be linked in other ways. Some researchers have suggested that a diagnosis of HIV infection may trigger violence at the time of disclosure to significant social relationships.…”
Section: Violence Victimization After Hiv Infection In a Us Probabilimentioning
confidence: 99%
“…The DTES in Vancouver is one of the most economically disadvantaged neighbourhoods in Canada, and as such has the lowest per capita income of any urban region in the country (Statistics Canada, 1996). Homelessness, a common feature of this and many other impoverished neighbourhoods, has been recognized as a major determinant of poor health among IDU, including an elevated risk of HIV infection (Fisher et al, 1995;Rhodes et al, 2005;Zolopa et al, 1994). The observed association between homelessness and violence may be attributed to a variety of factors.…”
Section: Discussionmentioning
confidence: 99%
“…Second, homeless individuals may have to engage in income generation activities that carry increased risk for violence (e.g., petty crime, sex work) (Erickson, 2001;Johnson et al, 1985). Finally, homeless individuals are more likely to participate in the street-based drug economy (Fisher et al, 1995;Wechsberg et al, 2003), a culture which has been associated with the normalization of extreme levels of violence (Bourgois et al, 2004). Further research must be conducted to elucidate the multi-level factors that perpetuate both homelessness and violence within disadvantaged and drug using populations.…”
Section: Discussionmentioning
confidence: 99%
“…Homelessness is associated with several traumatic life events including physical and sexual violence (Browne, 1993;Fisher et al, 1995;Lee & Schreck, 2005;North et al, 1994;North et al, 1996;Nyamathi et al, 2001;Wenzel et al, 2001;Zugazaga, 2004). Of 961 homeless women, just over a third (34%) reported experiencing major physical violence in the past year, and half of those women reported experiencing more than one assault during that time .…”
Section: Homelessness: An Important Exosystem Factormentioning
confidence: 99%